Single Entry Approach (SEnA): Remedial Measure to Peaceful and Speedy Labor Dispute Settlement in the Philippines - Bañares, Stella Maris P. (Philippine Journal of Labor and Industrial Relations, 2021)
Generally, the purpose of this article is to fill the gap by highlighting the current state of labor dispute resolution in the country, which uses the Department of Labor and Employment’s newest program called the Single Entry Approach (SEnA), and by explaining in detail the steps involved in the process. The paper is designed to specifically provide information on the latest trend in dispute settlement. Using the information gathered from the interviews, papers, news articles, journals and other reading materials, the principles of the program and all the intrinsic details of how the program works, and its impact on and significance to its end-users or stakeholders was comprehensively discussed. SenA is described as the simplified and the most effective and efficient way of resolving labor dispute conflict in the workplaces. It defines how the conciliation-mediation method using SEnA can be used as a very effective alternative tool in dispute resolution. It centered mainly on the findings, observations, discussions and highlights particularly related to the advantages and disadvantages of the program, and the characteristics that conciliators and mediators must possess in order to effectively implement and execute the program. The recommendations, on the other hand, tried to deliver the practical implications and applications of the findings that can further develop or enhance the program.The in-depth interviews and qualitative data analysis, including the graphs and charts, revealed important information extracted mostly from officials of the Conciliation and Mediation Unit of the National Capital Region. All of them possess the knowledge and expertise gained from a minimum of 11 years to more than 20 years of experience in the field of conciliation, mediation, and other modes of alternative dispute resolution mechanisms.